PERBANDINGAN PENGARUH LATIHAN ANTARA PASSING BAWAH BERPASANGAN DENGAN PASSING BAWAH PERORANGAN TERHADAP KETERAMPILAN PASSING BAWAH PADA TIM BOLA VOLI PUTRA SMAN 1 PEKANBARU - Sanjaya, Egi; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is that the lower passing skill of male volleyball team SMAN 1 Pekanbaru is considered to be poor, it could be seen when the team was attempting to catch the lower passing ball by the teammate, and also the ball movement was not correct. This is an experimental research, population used for this research is male volleyball team of SMAN 1 Pekanbaru, and a total of 12 players was contributed as samples. The data needed was collected from pre-test and post-test. The instrument of this research is a lower pass to the wall to measure their skill on it. The variables of this research are paired and individual lower passing as independent variable (X) and lower passing skill as dependent variable (Y). data collected was processed statistically to examine the normality by using liliefors test at 0,05α significance level. Hypothesis proposed was there is an impact on doing paired and individual lower passing exercise to lower passing skill. Referred to t-test analysis, it is concluded: 1) Tcount 9,42 > Ttable 2,015, 2) Tcount 12,15 > Ttable 2,015, 3) Tcount 4,28 > Ttable 1,812. In conclusion, Ho is rejected and HI is accepted, it has shown a significant impact of paired and individual lower passing training to lower passing skill on male volleyball team of SMAN 1 Pekanbaru.Keywords: Paired and Individual Lower Passing Training